Rediagnosis of Ichthyotrema Caballero & Bravo-Hollis, 1952 (Digenea: Gyliauchenidae Fukui, 1929), including the redescription of I. vogelsangi Caballero & Bravo-Hollis, 1952 - Hall, Kathryn A.; Cribb, Thomas H. (Zootaxa, 2007)
Recent studies on the Gyliauchenidae Fukui, 1929 have lead to our reinterpretation of the morphology of the group. Here we emend the generic diagnosis of Ichthyotrema Caballero & Bravo-Hollis, 1952 to reflect current understanding of the morphology of the digestive system and male terminal genitalia. We redescribe the type-, and only, species, Ichthyotrema vogelsangi Caballero & Bravo-Hollis, 1952, based on our examinations of paratype material from the intestine of Prionurus punctatus Gill, 1862, caught in Pacific waters off Mexico. Specimens of I. vogelsangi are distinctive because of their massive bodies, and Ichthyotrema is distinguished among the Gyliauchenidae by the position of the cirrus-sac entirely posterior to the caeca, the possession of a post-testicular ovary and the coiling of the uterus between the diagonal testes. The ventral sucker of Ichthyotrema is close to the posterior extremity of the body, supporting placement of the genus within the Gyliaucheninae Fukui, 1929. Here we recognise Ichthyotrema as a monotypic genus within the Gyliauchenidae, which is restricted to acanthurid fishes in the Eastern Pacific Ocean.